Application of Lean Manufacturing in the Canned Food and Beverage Industry: Literature Review - Angelia Anggia Permata Norman; Kuncorosidi Kuncorosidi; Risma Rosmalia (STIESA Press, 2023)
Food and beverage companies can increase profit margins by using recycled packaging, introducing scalable solutions, and implementing appropriate management systems. Canned food is any form of food that has been perfectly processed or minimally processed which is stored in a hermetically closed container (cans, pouches, etc.) and undergoes sterilization. This method of food preservation was developed in the late 18th century. Implementing lean manufacturing properly could help the company provides high-quality product at minimum cost without reducing the value-added for customers. The purpose of this study is to determine the principles of Lean Manufacturing in the canned food and beverage industry and to determine the reduction of waste in the canned food and beverage industry. The research method is a literature review, with keywords: lean manufacturing, the canned food and beverage, packaging, and lean manufacturing tools. There are 20 reference journals that support the research. The results showed that (1) the principle of lean manufacturing in the canned food and beverage industry as an illustration that improvements to the can packaging process in the food and beverage industry can significantly reduce waste, (2) lean manufacturing can be used to eliminate waste and improve the production process using the 5S method which serves to prevent and facilitate companies in detecting problems that will arise.), (3) lean manufacturing has been widely applied in various industries, especially in the canned food and beverage industry